The Effects Of Oil Price On Oil-Consuming Countries’ Economies Before Russia-Ukraine War: The Study Of Belarus And Portugal - Olga PLESKATSEVICH; Nuno MOUTINHO (Communications of International Proceedings, 2023)
The development of economies has been linked to the capacity to use energy. Oil has a significant impact on everyday life and oil price fluctuations are of concern to all countries because they have a major impact on countries' economies. Because oil prices have daily fluctuation with impact on demand, this study analyses the effects of oil prices on the main macroeconomic indicators of two oil-consuming countries before the war between Russia and Ukraine. Given that Belarus and Portugal have different macroeconomic contexts, it is assumed that a change in oil prices will have different effects on each country's economy. We use Vector Autoregression (VAR) models to show that changes in oil prices have a negative impact on the economic development of both countries. We also conclude that oil price shocks have a more profound effect on the Portuguese economy than on the Belarusian economy. Although oil prices have negative effects on macroeconomic indicators in both countries, these are more profound in Portugal. Furthermore, the negative impact is greater in the short term and weakens over the years. Based on a period before the war between Ukraine and Russia, this work provides valuable information for governments about the impact of oil prices and evidence the short-tern and long term effects.
Keywords: Oil price; Macroeconomic indicators; VAR model